2009
DOI: 10.1016/j.ijms.2009.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Determination of polar 1H-benzotriazoles and benzothiazoles in water by solid-phase extraction and liquid chromatography LTQ FT Orbitrap mass spectrometry

Abstract: Determination of polar 1H-benzotriazoles and benzothiazoles in water by solid-phase extraction and liquid chromatography LTQ FT Orbitrap mass spectrometry van Leerdam, J.A.; Hogenboom, A.C.; van der Kooi, M.M.E.; de Voogt, W.P. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 11 publications
5
84
2
1
Order By: Relevance
“…One year later, Hogenboom and co-workers [89] explored the characteristics of the Orbitrap for accurate mass screening and identification of emerging contaminants in environmental samples. The same group also published quantitative applications using the Orbitrap analyzer [90]. A recent trend paper summarizes both quantification of target analytes and identification of unknowns using the Orbitrap mass analyzer [14].…”
Section: Environmental Applications Of Lc-hrmsmentioning
confidence: 99%
“…One year later, Hogenboom and co-workers [89] explored the characteristics of the Orbitrap for accurate mass screening and identification of emerging contaminants in environmental samples. The same group also published quantitative applications using the Orbitrap analyzer [90]. A recent trend paper summarizes both quantification of target analytes and identification of unknowns using the Orbitrap mass analyzer [14].…”
Section: Environmental Applications Of Lc-hrmsmentioning
confidence: 99%
“…In addition, we have shown the occurrence of emerging polar contaminants, such as benzotriazoles and metabolites of illicit drugs (e.g. benzoylecgonine, desalkylflurazepam and 9-carbonic acid-d-9-THC) in groundwaters and surface waters in the Netherlands Van Leerdam et al, 2009). …”
Section: Introductionmentioning
confidence: 98%
“…On account of their low sorption capacity (Hart et al 2004), BTs occur mostly in the aquatic environment Kiss and Fries 2009;Reemtsma et al 2010;Janna et al 2011;Kiss and Fries 2012). However, the mobility of these polar compounds in the environment is still not well characterized, although their presence in ground water (Cancilla et al 1998;Hollender 2007), bank filtrate (Reemtsma et al 2010), and drinking water have already been reported (van Leerdam et al 2009). …”
Section: Benzotriazoles and Benzothiazolesmentioning
confidence: 99%
“…Slightly higher LODs were obtained in river water using SPE and comprehensive twodimensional GC coupled with time-of-flight mass spectrometric (GCxGC-TOF-MS; Jover et al 2009). A method based on SPE and LC coupled with an LTQ-FT-Orbitrap MS allowed quantifying BT in drinking and surface water down to a LOD of 10 ng L -1 (van Leerdam et al 2009). To avoid time-consuming extraction and cleaning steps, the determination of BTs in directly injected river water and waste water samples was applied successfully using LC-ESI-MS/MS (Weiss and Reemtsma 2005).…”
Section: Benzotriazoles and Benzothiazolesmentioning
confidence: 99%
See 1 more Smart Citation